Seated by the Sea : The Maritime History of Portland, Maine, and Its Irish Longshoremen - Connolly, Michael (Book collections on Project MUSE., 2010)
Traces the rise of the Irish-American immigrant community in Portland, Maine, through its control of waterfront labor over eight decades before the port's twentieth century decline.